2016
DOI: 10.5194/isprsarchives-xli-b7-371-2016
|View full text |Cite
|
Sign up to set email alerts
|

A Fuzzy Logic-Based Approach for the Detection of Flooded Vegetation by Means of Synthetic Aperture Radar Data

Abstract: ABSTRACT:In this paper an algorithm designed to map flooded vegetation from synthetic aperture radar (SAR) imagery is introduced. The approach is based on fuzzy logic which enables to deal with the ambiguity of SAR data and to integrate multiple ancillary data containing topographical information, simple hydraulic considerations and land cover information. This allows the exclusion of image elements with a backscatter value similar to flooded vegetation, to significantly reduce misclassification errors. The fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…For subregions where bimodality is satisfied, Otsu thresholding is applied to classify pixels into foreground and background (or flooded and dry). We then applied a few post-processing steps to remove false-positive (pixels that are classified as flooded but should be dry) pixels with some commonly used geo-topo indexes in RS-based flood mapping applications (Tsyganskaya et al, 2016(Tsyganskaya et al, , 2018. We recommend moderate adjustment of those indexes in order to get satisfying results for different regions.…”
Section: Rs-based Flood Mapping With Qfr Proceduresmentioning
confidence: 99%
“…For subregions where bimodality is satisfied, Otsu thresholding is applied to classify pixels into foreground and background (or flooded and dry). We then applied a few post-processing steps to remove false-positive (pixels that are classified as flooded but should be dry) pixels with some commonly used geo-topo indexes in RS-based flood mapping applications (Tsyganskaya et al, 2016(Tsyganskaya et al, , 2018. We recommend moderate adjustment of those indexes in order to get satisfying results for different regions.…”
Section: Rs-based Flood Mapping With Qfr Proceduresmentioning
confidence: 99%
“…Although the natural breaks can handle volumes of spatial data, this method required predefined numbers of intervals before the discretization process. There are numerous studies including works by various researchers (Chang & Tsai, 2016;Güçlü & Şen, 2016;Lohani, Kumar, & Singh, 2012;Pulvirenti, Pierdicca, Chini, & Guerriero, 2011;Tsyganskaya et al, 2016) that exploit the concept of fuzzy logic in model development for disaster management analysis. It has been shown that fuzzy logic is extensively applied to analyze complex patterns with high accuracy.…”
Section: Discretization Of Continuous Flood Inducing Factorsmentioning
confidence: 99%